2003
DOI: 10.1063/1.1544081
|View full text |Cite
|
Sign up to set email alerts
|

Laser transfer of biomaterials: Matrix-assisted pulsed laser evaporation (MAPLE) and MAPLE Direct Write

Abstract: Two techniques for transferring biomaterial using a pulsed laser beam were developed: matrix-assisted pulsed laser evaporation (MAPLE) and MAPLE direct write (MDW). MAPLE is a large-area vacuum based technique suitable for coatings, i.e., antibiofouling, and MDW is a localized deposition technique capable of fast prototyping of devices, i.e., protein or tissue arrays. Both techniques have demonstrated the capability of transferring large (mol wt>100 kDa) molecules in different forms, e.g., liquid and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(65 citation statements)
references
References 48 publications
0
60
0
4
Order By: Relevance
“…3−5 Previous work has also demonstrated that mammalian cells can be laser printed with no loss of viability or DNA damage. 7,[28][29][30]35,36 This manuscript describes further development of the BioLP TM technique that enables reproducible and accurate cell printing with single cell resolution. Growth curves and immunocytochemical results are also presented that indicate cells not only remain viable and have similar growth properties to nonprinted cells, but also do not express heat shock proteins that are often expressed by cells during and after various stressor conditions.…”
Section: Introductionmentioning
confidence: 99%
“…3−5 Previous work has also demonstrated that mammalian cells can be laser printed with no loss of viability or DNA damage. 7,[28][29][30]35,36 This manuscript describes further development of the BioLP TM technique that enables reproducible and accurate cell printing with single cell resolution. Growth curves and immunocytochemical results are also presented that indicate cells not only remain viable and have similar growth properties to nonprinted cells, but also do not express heat shock proteins that are often expressed by cells during and after various stressor conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts to achieve rapid cellular patterns without use of photolithography include: (1) laser-guided direct writing (Nahmias et al, 2004;Odde and Renn, 2000), (2) aerosol-based direct deposition of animal cells using CAD/ CAM manufacturing technology (Marquez et al, 2002), (3) biological laser printing (Barron et al, 2004), which stems from the matrix-assisted pulse laser evaporation direct write (MAPLE DW) method Wu et al, 2003), (4) aerosol-based direct deposition of animal cells through a mask (Nahmias et al, 2005), and (5) direct patterning of biomolecules using an inkjet printer (Roth et al, 2004). In laser-guided direct writing, individual living cells are directed onto a glass substrate by guiding the cells for approximately 1 mm through aqueous media using optical forces.…”
Section: Comparison To Other Emerging Cellular Patterning Methodsmentioning
confidence: 99%
“…Moreover, several LIFT variations have been reported over the last two decades such as the metallic or polymer dynamic release layer (DRL) LIFT (2)(3)(4)(5)(6)(7)(8), blister actuated laser-induced forward transfer (BA-LIFT) (9), laserinduced backward transfer (LIBT) (10), and MatrixAssisted Pulsed Laser Evaporation-Direct Write (MAPLE-DW) (11)(12)(13). The above-mentioned laser printing techniques can be often seen in literature under the general term "Laser Direct Write" (Figure 1), and they usually incorporate a pulsed laser, used to induce the transfer of the material of interest, as well as a donor and a receiver substrate, in proximity or in contact with each other.…”
Section: Introductionmentioning
confidence: 99%